The women on the 6th floor [videorecording (DVD)] = Les femmes du 6ème étage - Le Guay, Philippe, 1956-; Le Guay, Philippe, 1956-; Maura, Carmen, 1945-; Luchini, Fabrice, 1951-; Kiberlain, Sandrine; Verbeke, Natalia, 1975- (Strand Releasing, 2012)
Paris, 1960. Jean-Louis lives a bourgeois existence with his neurotic socialite wife Suzanne while their children are away at boarding school. The couple's world is turned upside down when they hire Maria, a Spanish maid who introduces Jean-Louis to an alternative reality a few stories up on the sixth floor. Befriending a group of sassy Spanish maids, the women teach him there's more to life than stocks and bonds, and their influence on the house ultimately transforms everyone's life.